Comparing the effects of hybrid and online learning on physical activity and body mass index: A quasi-experimental investigation - Putra, Muhamar Kodafi; Saputra, Adhe; Kuntarto, Eko; Sofyan (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2023)
Changes in learning methods at school can affect students' learning habits and activity patterns. This study aims to investigate the effect of hybrid learning compared to online learning on fitness level and body composition, specifically focusing on body mass index (BMI). The research method used was a quasi-experiment with a pretest-posttest control group design approach. The number of research subjects was 128 students with an average age of 10.35 ± 0.67 years, a body weight of 42.05 ± 8.97 kg, and a height of 142.84 ± 7.94 cm. The results showed that the post-test BMI score in the hybrid learning group decreased significantly, p < 0.05, by 19.69 kg/m2, and there was an increase in physical activity of 2.94 METs. Whereas in the online learning group, there was no significant difference in BMI or physical activity variables. The results of this study are expected to be a reference for teachers in schools and other educators to apply the hybrid method compared to online learning so that students' physical activity patterns can be maintained and continuously improved, which has an impact on body composition. The findings can also help in reducing physical activity patterns in big cities on the island of Sumatera and can be a discussion for researchers to create or modify more effective and efficient learning methods.